Manajemen Pendidikan & Kepemimpinan Pendidikan - Triwiyanto, Teguh (Proceedings Series of Educational Studies, 2024)
Abstract: The research objective is to synthesize educational management educational leadership. This research method is literature, the type used is traditional review. Search and compile library data using the Publish or Perish operator. Once the relevant literature has been collected, organize the retrieved articles systematically. After literature collection, the data analysis stage involves several techniques. Start by synthesizing information gathered from selected articles to identify common themes, trends, and theoretical frameworks relevant to educational management and leadership. The research results show that educational management includes a variety of components, each of which plays an important role in effective bureaucracy and educational institutions. One type of fundamental component is structural, which includes aspects such as organizational hierarchy, physical infrastructure, and resource allocation. Structural components form the framework within which educational bureaucracies operate, determining how tasks are delegated, facilities are used, and budgets are managed. Educational leadership consists of various components that are integral to fostering a positive learning environment and driving institutional success. One type of important component is visionary leadership, which involves establishing a compelling vision for the future direction of an educational institution.Abstrak: Tujuan penelitian untuk mensintesiskan manajemen pendidikan kepemimpinan pendidikan. Metode penelitian ini yaitu pustaka, jenis  yang digunakan adalah traditional review. Pencarian dan pengmuplan data pustaka dengan memanfaatkan operator Publish or Perish. Setelah literatur yang relevan dikumpulkan, atur artikel yang diambil secara sistematis. Setelah pengumpulan literatur, tahap analisis data melibatkan beberapa teknik. Mulai dengan mensintesis informasi yang dikumpulkan dari artikel-artikel terpilih untuk mengidentifikasi tema-tema umum, tren, dan kerangka teoritis yang relevan dengan manajemen dan kepemimpinan pendidikan. Hasil penelitian menunjukkan manajemen pendidikan mencakup beragam komponen, yang masing-masing memainkan peran penting dalam birokrasi dan lembaga pendidikan yang efektif. Salah satu jenis komponen mendasar adalah struktural, yang mencakup aspek-aspek seperti hierarki organisasi, infrastruktur fisik, dan alokasi sumber daya. Komponen struktural membentuk kerangka di mana birokrasi pendidikan beroperasi, menentukan bagaimana tugas didelegasikan, fasilitas digunakan, dan anggaran dikelola. Kepemimpinan pendidikan terdiri dari berbagai komponen yang merupakan bagian integral untuk menumbuhkan lingkungan belajar yang positif dan mendorong keberhasilan institusi. Salah satu jenis komponen penting adalah kepemimpinan visioner, yang melibatkan penetapan visi yang meyakinkan untuk arah masa depan lembaga pendidikan.